HIGH-FREQUENCY CUTOFF IN TYPE III BURSTS - Stanislavsky, A. A.; Konovalenko, A. A.; Volvach, Ya. S.; Koval, A. A. (Одеські астрономічні публікації, 2016)
In this article we report about a group of solar bursts with high-frequency cutoff, observed on 19 August of 2012 near 8:23 UT, simultaneously by three different radio telescopes: the Ukrainian decameter radio telescope (8-33 MHz), the French Nançay Decametric Array (10-70 MHz) and the Italian San Vito Solar Observatory of RSTN (25-180 MHz). Morphologically the bursts are very similar to the type III bursts. The solar activity is connected with the emergency of a new group of solar spots on the far side of the Sun with respect to observers on Earth. The solar bursts accompany many moderate flares over eastern limb. The refraction of the behind-limb radio bursts towards the Earth is favorable, if CMEs generate low-density cavities in solar corona